Analisis Tingkat Kesejahteraan Buruh Nelayan di Kecamatan Bantur Kabupaten Malang - Iik WIdya Andriani; Ida Nuraini (Jurnal Ilmu Ekonomi, 2021)
This study aims to Know the Fishermen Welfare Level in Bantur District, Malang Regency. This research was conducted in Bantur District, Malang Regency. The population in this study were fishermen who were in Bantur District, Malang Regency, especially labor fishermen. The sample in this study was 30 families, especially labor fishermen. Data collection techniques used were questionnaires. The data analysis technique used is descriptive qualitative analysis. The results showed the level of welfare of fishermen measured using the Fisherman Exchange Rate (NTN) of labor fishermen in Bantur District, Malang Regency which was 154 where > 100, it can be said that all respondents were prosperous. Fishermen Exchange Rates are fluctuating, where the size is greatly influenced by the season, the lack of electricity supply, bad weather conditions and the scarcity of fuel supplied to fishing vessels. including fishing gear that has expired.